2021
DOI: 10.21273/hortsci15115-20
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Productivity of ‘Consort’ Black Currant Grown under Varying Levels of Artificial Shade

Abstract: The shade tolerance of black currants (Ribes nigrum cv. Consort) was studied by measuring the growth and productivity of mature plants in the field for three seasons under full sun or artificial shade netting in Urbana, IL. Shade treatments reduced photosynthetically active radiation (PAR) from 37% to 83%. Yield was not reduced in shade levels up to 65% but decreased by as much as 66% under 83% shade. Shade had minimal effect on stem rejuvenation in the first 2 years, but reduced rejuvenation in the third year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The results indicated that shaded jujube leaves obtained higher light energy by increasing photosynthetic pigment contents and meanwhile improved photosynthetic phosphorylation activity by reducing the chl a/b ratio [30,31]. However, the decrease in specific leaf weight in jujube leaves indicated that the enhanced capacity for light capture did not compensate for the reduction in leaf photosynthesis caused by shading, which was similar to results from studies of black currant, grape, and cigar tobacco leaves [32][33][34].…”
Section: Shading Increased Photosynthetic Pigment Contents Of Leaves ...supporting
confidence: 76%
“…The results indicated that shaded jujube leaves obtained higher light energy by increasing photosynthetic pigment contents and meanwhile improved photosynthetic phosphorylation activity by reducing the chl a/b ratio [30,31]. However, the decrease in specific leaf weight in jujube leaves indicated that the enhanced capacity for light capture did not compensate for the reduction in leaf photosynthesis caused by shading, which was similar to results from studies of black currant, grape, and cigar tobacco leaves [32][33][34].…”
Section: Shading Increased Photosynthetic Pigment Contents Of Leaves ...supporting
confidence: 76%
“…In agroforestry systems, berry shrubs can be planted between the rows of trees, typically coming into production years before the nut trees are yielding heavily. Some species such as black currant ( Ribes nigrum ) can maintain productivity even when the overstory trees are large enough to compete for light (Wolske et al 2021 ). In addition to focusing on shrub species with the greatest potential impacts on chronic diseases, characteristics such as productivity, shade tolerance, adaptability to the area, and low maintenance requirements should be considered when introducing berry shrubs into an agroforestry system.…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, all treatments reached peak ripeness similarly and were harvested on July 6th. For more information on methods and results relating to the yield and phenology of this study consult [ 22 ]. Subsamples of 300 berries per bush were removed for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Currants occur naturally in understory environments and are known to produce and grow well under shaded conditions [ 19 , 20 , 21 ]. The growth and productivity of black currants was maintained in up to 65% shade as found by [ 22 ]. Previous research on black currant berry quality in response to shade has shown a reduction in berry sucrose and glucose sugars, with an increase in citric acid in deep shade [ 19 ].…”
Section: Introductionmentioning
confidence: 90%